Analilis Koperatif Capaian Literasi Dan Numerasi Siswa Berdasarkan Data Raport Pendidikan 2023-2025 - Ibrahim Kale Hedo; Prety Gracia Dara; Ribka Snae (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aims to comparatively analyze student literacy and numeracy achievement across educational levels (SD/MI, SMP/MTs, SMA/MA, and SMK) based on the Education Report Card (Rapor Pendidikan) data for 2023, 2024, and 2025, published by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia. A quantitative descriptive-comparative research method with secondary data analysis was employed. Analytical techniques included descriptive statistics (mean, standard deviation, category distribution), Kolmogorov-Smirnov normality test, Levene homogeneity test, one-way ANOVA, paired t-test, and Pearson correlation analysis. Results revealed a statistically significant upward trend in mean literacy scores (55.52 → 61.09) and numeracy scores (50.18 → 56.62) during 2023–2025 (p < .05). One-way ANOVA demonstrated significant differences in achievement across educational levels (F = 18.73; p < .001 for literacy; F = 16.21; p < .001 for numeracy). A very strong positive correlation was found between literacy and numeracy scores (r = .891; p < .001) in 2025. Senior high schools (SMA/MA) consistently recorded the highest achievement, while primary schools (SD/MI) recorded the lowest in both dimensions. These findings underscore the need for more intensive data-driven interventions at the primary level and integrated reinforcement of literacy-numeracy programs.